The Impact of the University in Increasing the Book Reading on Students: Case Study Soran University - Şakir İşleyen; Amir Khaleel Hassoo (Budapest International Research and Critics University, 2020)
Reading is perusing through texts to understand concepts. In the event that you battle to centre, reading can improve your attention span. Books with better structures encourage us to think in sequence the more we read, the more our brains are able to link cause and effect. The main aim of this study is to investigate the effective factors that the role of the university in reading books. The sample of the study includes all the students at Soran University. The focused on populace size for the investigation is 400 understudies who chose haphazardly. The acquired information were broke down with the SPSS program by using methods containing descriptive statistics, Chi-square test. The results indicated some factors such as good communication between reading a book and students, offering university and professional development courses with a variety of skills for students, The research includes “Individual Reasons”, “age group”, “Perusing material during recreation time”, “Department”, play a significant role in reading book students in the university.